استخدام العناصر التراثية والمحلية في الفن العربي المعاصر - نجوى أحمد (Tishreen University, 2019)
بين المعاصرة والبحث عن التراث, انتشر في الفن العربي ظاهرة استخدام العناصر التراثية في فنون التصوير, الحفر, والإعلان, ولكن على الأغلب كانت تلك المساعي مشتتة وغير ناضجة.... إذ لا توجد حداثة لدى شعب عريق إلا وهي تحوي بعضاً من الخلفيات والتأثيرات التراثية والمحلية وعلينا إبطال مقولة أن الاختلاف مع الفن الغربي - والذي طالما تأثرنا به - يعتبر ابتعاداً عن التفوق والإبداع. وفي مقارنة بسيطة بين الفن الغربي والفن العربي نقول: إن ظهور الأكاديميات الفنية العريقة التي حملت مسؤولية تعليم وتخريج فنانين متميزين ومخلصين للقيم الفكرية الغربية, جعلت كل من خرج عن قيمها الأكاديمية منبوذاً.... ولم يكن موفقاً استخدام العناصر التراثية والمحلية بتقنيات المدارس الغربية بشكل مباشر, وإنما يحتاج الفنانون إلى التجريب والعودة إلى دراسة الموروث التراثي، وتصنيفه بمساعدة النقاد بالمؤتمرات والندوات.   In its attempt to be both contemporary and true to its origin, Arabic art uses traditional Arabic elements and contemporary Western ones.  Traditional elements of painting- graphic sculpture- and postals were popular, though mostly in an immature or disorganized way. A brief comparison between Western art and Arabic art shows that old Art Academies from which distinguished artists, faithful to Western intellectual values have graduated, ostracized any artist that did not follow their academic values. At the same time, Arabic Islamic culture was moving away from figuration and to focus, instead, on the spiritual dimension as well as on architecture, the art of books and drawing in books. Thus, schools of Islamic miniatures, whose perspective was different from the European perspective, appeared. Nevertheless, the use of local and traditional elements did directly appropriately benefit from the techniques of Western schools. Arab artists need to experiment and restudy the traditional heritage and classify it, aided by critics, conferences and symposium.